Culture, motivation, and learning : a multicultural perspective - Salili, Farideh; Hoosain, R. (Research in multicultural education and international perspectives., 2007)
The influence of culture on learning and motivation has been the topic of much research in recent years. Educational and psychological researchers are now aware that the findings of their studies may not apply to other cultures, and that in this age of globalization and multiculturalism it is very important to examine the applicability of psychoeducational constructs to other cultures. Understanding learning and motivational characteristics of students of diverse backgrounds will enable educators to develop appropriate curriculum and teaching strategies to motivate these students.The aim of this book is to present research findings and views of scholars and researchers in the field of motivation and learning, from a multicultural and international perspective. Educators and scholars from different parts of the world have examined recent learning and motivation theories in different cultural contexts in order to explore the dynamics of sociocultural processes affecting student motivation. Others have focused on teaching and learning strategies that are known to be effective with culturally diverse students.